Building consensus on identifying research mentoring gaps and finding ways of addressing the gap in a Kenyan college of health sciences - Masemiano P. Chege (AOSIS, 2019)
Background: The concept of mentoring in clinical practice has traditionally focused on moving graduates from novice to more respectable positions within the clinical practice hierarchy. With the growing emphasis on evidence-based practice, the role of research in generating evidence for practice cannot be overemphasised. Mentoring in clinical operational research for both students and junior members of academic staff in health professionals' training colleges is as important as mentoring for clinical skills. Aim: This study aimed at building consensus on possible ways of enhancing research mentoring for graduate students and members of academic staff in a college of health sciences. Setting: The study was conducted within Moi University College of Health Sciences (MUCHS) in Eldoret, Kenya. Methods: The study population was composed of academic staff members and registered graduate students by the end of 2015. All academic staff and graduate students were eligible to participate. The Delphi technique was used to not only collect individual opinions but also build consensus. During the first iteration, questions were sent for which open-ended responses were needed. Responses from the first round were grouped into patterns and themes that guided the writing of questions for the subsequent rounds. Results: The response rate was 78%. There was consensus in appreciating that mentoring was fundamental for career growth in clinical practice and research and needed for improving and developing formal structure for effective mentoring. It was crucial to establish training programmes for mentors and for accrediting them. Conclusion: Enhancing of current research mentoring in MUCHS was needed and expected by graduate students and academic staff.